PP-P DIFFERENTIAL TRAVELTIME MEASUREMENT WITH CRUSTAL CORRECTION - Obayashi M.; Suetsugu D.; Fukao Y. (My University, 2004)
PP-P differential traveltime data are useful for constraining the seismic structure of the upper mantle. The cross-correlation method has been used for these measurements, whereby a synthetic PP waveform is constructed from the observed P and is cross-correlated with the observed PP. PP waveforms are, however, distorted by interference with the precursors and post-cursors produced by reflections and conversions at crustal discontinuities. Accordingly, the measurement of PP-P differential traveltimes can suffer a bias. Synthetic experiments have shown that this bias becomes significant when seismograms are lowpass filtered. To measure PP-P differential times without such bias, we developed a method to take crustal effects into consideration in the cross-correlation method. In this new method, the response of incident P to the crustal structure beneath the PP bounce point is calculated and convolved with the observed P in constructing the synthetic PP waveform. As an experiment we applied this to real seismograms lowpass filtered with corners at 0.5, 0.1 and 0.05 Hz. We took crustal models from the global database CRUST2.0. This experiment shows that the method is effective in reducing the bias in traveltime measurements, even for measurements with long period waveforms below 0.05 Hz. With the assumption that the crustal structure is described by CRUST2.0, the application of our method to the observed seismograms provides PP-P values mutually consistent among the measurements using three different lowpass filters with corners at 0.5, 0.1 and 0.05 Hz.
Keywords: BODY WAVES; CRUSTAL STRUCTURE; EARTH'S INTERIOR; PPP